Internal Control Systems and Financial Accountability in Government Business Enterprises: A Case of National Water and Sewerage Corporation Ntungamo Area. - Alexander, Kujuna (Kabale University, 2022)
A Dissertation Submitted in Partial Fulfilment for the Requirment of the Award of a Degree of Master of Business Administration of Kabale University